2020
DOI: 10.3390/polym12040770
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Scaffold onto Titanium Implants. A Versatile Strategy Increasing Biocompatibility

Abstract: Osseointegration of metal prosthetic implants is a yet unresolved clinical need that depends on the interplay between the implant surface and bone cells. The lack of a relationship between bone cells and metal has traditionally been solved by coating the former with “organic” ceramics, such as hydroxyapatite. A novel approach is hereby presented, immobilizing covalently dendrimeric structures onto titanium implants. Amide-based amino terminal dendrons were synthetized and coupled to titanium surfaces in a vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…At present, the osseointegration of titanium implants is a problem that remains to be solved. Molina et al [ 63 ] immobilized covalent dendrimers on titanium implants, synthesized amide-based amino-terminal dendrites, and coupled them to the titanium surface in a controllable manner. The dendritic portion anchored to the implant surface provides a scaffold for extracellular matrix (ECM) protein components that facilitate cell adhesion and proliferation.…”
Section: Metallic Biomaterials For Ammentioning
confidence: 99%
“…At present, the osseointegration of titanium implants is a problem that remains to be solved. Molina et al [ 63 ] immobilized covalent dendrimers on titanium implants, synthesized amide-based amino-terminal dendrites, and coupled them to the titanium surface in a controllable manner. The dendritic portion anchored to the implant surface provides a scaffold for extracellular matrix (ECM) protein components that facilitate cell adhesion and proliferation.…”
Section: Metallic Biomaterials For Ammentioning
confidence: 99%
“…1,2 However, titanium alloys are susceptible to bacterial infections, leading to complications or even fixation failure. 3 Postsurgical infection is one of the most dreaded problems of orthopedic procedures. 4 For addressing the problem of postsurgical infection, the clinical treatment for patients often relies on long-term antibiotics and multiple surgical debridement procedures, which causes the generation and spreading of multidrug-resistant (MDR) bacteria and causes pain and suffering to patients and heavy economic burden to the family and society.…”
Section: Introductionmentioning
confidence: 99%
“…The success rate of dental implants depends on osseointegration, which is initiated by cell adhesion when the implant surface meets the surrounding tissue [1][2][3][4][5][6][7]. Osseointegration failure is characterized by the instability or loosening of the implant, periimplantitis, and bone resorption [1,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of RGD peptides to bind with integrin receptors leads to increased cell adhesion and its functions [6,20]. It was reported that the tetrapeptide Gly-Arg-Gly-Asp (GRGD) peptide sequence derived from fibronectins will bind to integrins and other ECM proteins [5]. Moreover, the GRGD peptide was also reported to be useful in modifying the Ti implant surface [21].…”
Section: Introductionmentioning
confidence: 99%